An overview of the judicial control of state executive power - Sinani, Blerton (Array, 2019)
Many analyses and international reports point out that there is a significant lack of judicial control over the state executive power in the Republic of North Macedonia. This article aims to analyze the deficiencies that contribute to the lack of control, and special attention is also devoted to the administrative judiciary as a basic external form of providing judicial control over the legality of the decisions of public authorities and their officials, in order to ensure objective legality, as well as the protection of individual rights of citizens against unlawful administrative acts and actions of public administration. The first part of the article focuses on challenges for judicial control of the executive government. It shows the results of semi-structured interviews conducted with 36 stakeholders such as judges and prosecutors about the limits to judicial control of the executive. The second part focuses on weaknesses and challenges of the administrative judiciary, and makes proposals on how to improve the administrative judiciary as a special type judiciary within the framework of the judicial system of the Republic of North Macedonia. Therefore, it presents a crucial illustration to detect the specific problems and to offer possible solutions.